Evaluating Zakat Institutions Performance in Malaysia - Sayed Ahmed, Ebtehal Atta Elsayed; Yuserrie, Zainuddin (Universiti Malaysia Pahang, 2017)
This paper aims to evaluate the performance of zakat institutions in Malaysia in order to identify our need to develop its management systems. The development of zakat management institutions in Malaysia should be in line with the development of other sectors in the country. Changes that occurred in the administration in different institutions requires the Department of Zakat and religious councils to be more aware to face this changes and achieve the goals it has taken upon itself, such as product high quality Services , gain a wider audience of Zakat payers and meet needs of a larger number of poor and needy, At a time when poverty became one of the biggest problems facing societies. When we guide zakat institutions to adopt alternative mechanisms or advanced in the administration, we in fact pay it to confront the inadequacies problems dogging the current administrations in the performance of work which impedes economic and social development in the community in Malaysia